LITERASI DIGITAL PENDIDIKAN SEKSUALITAS PADA KONTEKS PERKAWINAN KATOLIK - Fransesco Agnes Ranubaya (Aggiornamento, 2021)
In this paper, the author concentrates on the theme of digital literacy in sexual education by context of Catholic marriage. This Literacy is not only the ability to read and write, but also the ability to understand and use information in various formats that come from various digital sources presented through computers. In the relation between digital literacy and sexuality education in the context of Catholic marriage, the author presents various digital literacy media that can be used to obtain information about sexuality education through the internet, both in general and in the context of Catholic marriage. Therefore, in this paper, the author hopes that the use of digital literacy will continue to be carried out as an intellectual habituation within the framework of modern studies today. The method of writing this article uses qualitative analysis with a documentation approach and critical analysis. The results of the research in this article show that digital literacy is very important to direct the correct understanding of sexuality education in the context of Catholic marriage. Therefore, every Catholic couple must have digital literacy skills so that their marriage remains eternal as aspired by the Catholic Church.